Re-Examining an Air Mass-Based Approach to Detecting Structural Climate Change, 1948-2011 - (:unkn) unknown (My University, 2014)
Air mass-based approaches to observing changes in climate can have considerable value beyond simple trends of temperature and moisture, providing more thorough understanding of structural climate patterns. Few methodologies have adequately characterized recent air mass modification, however. This research seeks to update and improve upon the methods of a prior study, providing new data from 1948-2011, as well as more rigorous statistical analyses. Air mass types were created, and monthly averages of temperature, dewpoint, and relative frequency were calculated for each of the air masses in all four seasons; then the time series were submitted to regression analysis. The results of this re-analysis show an increase in warm air masses at the expense of cool air masses coinciding with the patterns of surface temperature and air mass warming seen in other recent studies. Some changes in the behavior of these air masses were noted, however, along with new variations in the character of others. These air mass trends have conceivable ties to prior general circulation patterns. Assuming that previous patterns have continued a possible increase in troughs, with a simultaneous decrease in ridges, in the western United States may be occurring, while new patterns of air mass source region modification and air mass mixing could also exist. Systematic warming of air masses also has conceivable, though rather modest relationships with large scale circulation patterns, including positive phases of the Arctic Oscillation (AO) and North Atlantic Oscillation (NAO), as well as contraction of the circumpolar vortex.
Keywords: Air Mass; Climate Change; Integrated Method; Synoptic Climatology